Description of Spiritual Coping in Patients with Diabetic Foot Ulcer at the Wound Care Clinic In Makassar City - Nurul Hidayah; Saldy Yusuf; Moh Syafar Sangkala; Sarina Musdiaman (Indonesian Contemporary Nursing Journal, 2020)
Intoduction: Diabetes Mellitus (DM) is one of a non-infectious disease that increases from year to year. One complication that occurs in DM is Diabetic Foot Ulcer (DFU). DFU patients cause not only physical effects but also to have psychological effects. One of which is stress. If the patient stress, it can cause one of them is high blood sugar levels, which can affect the wound healing process. To overcome this problem, we using coping, which in this study looks at how Spiritual Coping with DFU patients. This study aims to determine the overview of Spiritual Coping in Patients with Diabetic Foot Ulcer at the Wound Care Clinic in Makassar City. Method: This was s cross-sectional approach. Samples for this research is 52 respondents with consecutive sampling technique. This research was conducted for one month, from September to October 2019. The instrument used for this study was the BRIEF RCOPE questionnaire. Results: Our finding confirmed mainly participant living with DFU has a definite spiritual coping. Conclusion: Overall, patient living with DFU has adopted positive spiritual coping.